The Textual Discourse Analysis of Educational News on Kompas.com and Tempo.co in the Perspective of Norman Fairclough’s Critical Discourse Analysis - Jati Kurniawan, Mikael; Mardikantoro, Hari Bakti; Joko Santoso, Bernadus Wahyudi (Universitas Negeri Semarang, 2021)
The education is considered as the main point of progress of a nation. The news that is about education is a topic that is always discussed in almost every mass media. The aim of this research is to identify and analyze textual practices of educational news discourse on Kompas.com and Tempo.co media. The approach used in this study includes a methodological approach, namely qualitative descriptive, and a theoretical approach that is called Norman Fairglough's critical discourse analysis. Based on this study, the vocabulary aspect is found that the use of experience values includes the use of ideological and metaphorical vocabulary. The relational values which contain the use of euphemisms and formal-informal words, and expressive values which contains the use of positive and negative evaluation sentences in the text. The importance of this research for the society is to raise critical awareness of all information developing in the digital world